Circulating Levels of Vascular Endothelial Growth Factor A and Its Soluble Receptor in Patients with Biopsy-proven Nonalcoholic Fatty Liver Disease - ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (ELSEVIER SCIENCE INC, 2011)
Background and Aims. Vascular endothelial growth factor A (VEGF) is a multifunctional cytokine affecting angiogenesis and vascular function. The biological activity of VEGF is modulated by its soluble receptor VEGFR-1 (sVEGFR-1). We explored the associations of VEGF and sVEGFR-1 concentrations with liver histology in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD). Methods. The study was comprised of 99 patients with NAFLD and 75 healthy controls. Serum VEGF and sVEGFR-1 concentrations were measured using commercially available enzyme-linked immunosorbent assays. Results. Serum VEGF levels did not differ in patients with NAFLD (1882 +/- 942 pg/mL) compared with healthy controls (1985 +/- 945 pg/mL, p = 0.42). However, compared with healthy subjects, levels of sVEGFR-1 were significantly lower in patients with NAFLD (1.59 +/- 0.58 ng/mL vs. 1.16 +/- 0.34 ng/mL, respectively, p < 0.001). After allowance for potential confounders, serum sVEGFR-1 levels retained their independent significance as a predictor of liver fibrosis in patients with NAFLD (beta = -0.19; t = -1.81, p < 0.05). Conclusions. Our results show that patients with biopsy-proven NAFLD have a significant reduction in serum sVEGFR-1 concentrations that predict the degree of liver fibrosis, independent of potential confounders. (C) 2011 IMSS. Published by Elsevier Inc.
Keywords: Vascular endothelial growth factor; Nonalcoholic fatty liver disease; Liver fibrosis; Enzyme-linked immunosorbent assay; Steatohepatitis; METABOLIC SYNDROME; PLASMA-LEVELS; VEGF; ANGIOGENESIS; ASSOCIATION; STEATOHEPATITIS; HYPERTENSION; SFLT-1; CELLS; RISK